2020
DOI: 10.1002/ird.2474
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seepage loss from concrete lined irrigation canals in Punjab, Pakistan

Abstract: A significant amount of water is lost in canals due to seepage. This could be saved to irrigate barren land. This article presents the measured seepage data by the inflow-outflow method on seven so-called concrete-lined distributary canals in Punjab, Pakistan. A special feature of the inflow-outflow method is the relatively long lengths of the canal reaches (9 to 5 km), which is the longest one could find in the literature so far. The seepage in canals is also calculated using five empirical formulae. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…There are several issues in the canal irrigation system. The primary ones include lack of adequate water storage facilities and seepage from poorly lined and unlined canals (Saeed & Khan, 2014; Shah et al, 2020; Qureshi, 2011). Water theft both through diversions and warashikni (water theft by taking water out of turn) along the watercourse remain rampant despite daily records of water discharge along each channel and the prospect of imprisonment under the Canal and Drainage Act (Fatima et al, 2016; Mustafa, 2001; Shah & Shahid, 2019).…”
Section: Country Contextmentioning
confidence: 99%
“…There are several issues in the canal irrigation system. The primary ones include lack of adequate water storage facilities and seepage from poorly lined and unlined canals (Saeed & Khan, 2014; Shah et al, 2020; Qureshi, 2011). Water theft both through diversions and warashikni (water theft by taking water out of turn) along the watercourse remain rampant despite daily records of water discharge along each channel and the prospect of imprisonment under the Canal and Drainage Act (Fatima et al, 2016; Mustafa, 2001; Shah & Shahid, 2019).…”
Section: Country Contextmentioning
confidence: 99%
“…The water lost through only seepage reaches about 15.95 million m 3 monthly, representing 99% of all lost irrigation water. Shah et al [16] used the inflow-outflow method for seven concretelined distributary canals in Punjab, Pakistan, then compared his results with results from five empirical formulae. The comparison showed that the mean percent errors ranged from −20% to +19%.…”
Section: Introductionmentioning
confidence: 99%
“…Seepage losses can be estimated either by direct measurement or by empirical equations. A number of studies, experimental as well as theoretical, have been conducted in the past to estimate seepage losses from irrigation canals (Subramanya, Madhav, & Mishra, 1973; Pontin, Abed, & Weller, 1979; Sharma & Chawla, 1979; Deacon, 1983; Akkuzu, Unal, & Karatas, 2007; Chahar, 2007; Sarki, Memon, & Leghari, 2008; Arshad et al ., 2009; Akkuzu, 2012; Soothar et al ., 2015; Jamel, 2016; Mohsen & Mohammed, 2016; Patel, Sneha, & Upadhyay, 2016; Zhang et al ., 2016; Shah et al ., 2020). The inflow–outflow method is commonly used (an experimental method) for direct determination of seepage loss in the canal.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al . (2020) measured seepage losses using the inflow–outflow method in seven concrete‐lined canals in Punjab, Pakistan, and the measured seepage losses were compared with five empirical formulae, namely Davis–Wilson, Kostiakov, Moritz, Punmia, and Swamee. Further, the Swamee formula was modified using surface water width instead of canal width to calculate the dimensionless variable F , which resulted in reducing the mean percent error from −42% to 20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation